SEEKING WHAT MATTERS: DETERMINANTS OF CLIENTS' SATISFACTION IN OBSTETRIC CARE SERVICES IN PAKISTAN - Ali, Moazzam; Qazi, Muhammad Suleman; Seuc, Armando (Journal of Ayub Medical College Abbottabad, 2014)
Background: Aim of this study was to determine the dimensions of the service quality in the public hospitals and evaluate the determinants of client satisfaction in obstetric health in the context of Pakistan. Methods: The present research evaluates the application of an integrated client satisfaction model that draws mainly from the original SERVQUAL framework in obstetric health services. We conducted a cross-sectional study, in four public district hospitals in Pakistan, enrolling 1101 clients attending obstetric health care services. Measures of service quality and determinants of client satisfaction were factor-analysed and multiple regression analysis was used to test the hypothesis. Results: The client satisfaction increased significantly with increases in respondent's age, number of children, number of visits and with decrease in educational status. Factor analysis revealed five service quality dimensions; and multiple regression analysis showed that all five dimensions of service quality in obstetric care were significant in explaining client satisfaction. The most powerful predictor for client satisfaction was provider communication with clients, followed by responsiveness and discipline. Conclusions: Interventions aimed at improving client provider interaction would not only advance the clinical provision of services, but would also result in greater patient satisfaction with the services provided, leading to higher levels of facility utilization and continuity of care. Better client provider interaction can be accomplished at hospital's level through focused training of all cadre of service providers sensitizing them on clients' needs. Results also showed that the proposed framework is a valid and flexible instrument in assessing and monitoring service quality and enabling staff to identify where improvements are needed, from the clients' perspective. Keywords: Service quality, client satisfaction, obstetric health care, SERVQUAL, Pakistan